(untitled) (International Journal of Communication Systems and Network Technologies, 2024)
A compact slotted planar square ring-shaped micro strip antenna simultaneously suitable for point to point communication at 60 GHz is presented. The antenna is simulated by the software CST. CST, computer simulated technology simulator is employed to analyze the proposed antenna and simulated results on return loss, the radiation pattern and polar plot gain is presented. The simulation and measurement result met the IEEE 802.1lad standard operate in 60 GHz band for point to point communication. The measured results shows a return loss of -26.69 db, gain of antenna is 7.566 dB and the voltage standing wave ratio VSWR < 2 at 60 GHz indicating that the antenna is a good candidate for very high speed WLAN applications.